WORK AND EQUALITY IN BRAZIL: WOMEN’S FIGHT FOR EQUALITY IN LABOR RELATIONS IN THE 21ST CENTURY (Reflection and Critique Law Magazine, 2025)
This article aims to address equality and labor relations in the 21st century. The prejudice rooted in society over the decades will be addressed, in addition to the history behind the entire beginning of the female profession in Brazil. On the other hand, the topic of the various aspects of harassment in the workplace will also be addressed, such as: moral (organizational morale), sexual and psychological. The issue of discrimination and racial insults will also be on the agenda, seeking to assess the extent to which progress has been made and the challenges to be faced in the legal, political and social spheres. Furthermore, the topic related to violence today and its changes will be presented at the end of the article.